Parental Linguistic Input and Its Relation to Toddlers' Visual Attention in Joint Object Play: A Comparison Between Children with Normal Hearing and Children With Hearing Loss. (9th April 2019) - Chen, Chi‐hsin; Castellanos, Irina; Yu, Chen; Houston, Derek M.
Abstract : Parent–child interactions are multimodal, often involving coordinated exchanges of visual and auditory information between the two partners. The current work focuses on the effect of children's hearing loss on parent–child interactions when parents and their toddlers jointly played with a set of toy objects. We compared the linguistic input received by toddlers with hearing loss (HL) and their chronological age‐matched (CA) and hearing age‐matched (HA) normal‐hearing peers. Moreover, we used head‐mounted eye trackers to examine how different parental linguistic input affected children's visual attention on objects when parents either led or followed children's attention during joint object play. Overall, parents of children with HL provided comparable amount of linguistic input as parents of the two normal‐hearing groups. However, the types of linguistic input produced by parents of children with HL were similar to the CA group in some ways and similar to the HA group in other ways. Interestingly, the effects of different types of linguistic input on extending the attention of children with HL qualitatively resembled the patterns seen in the CA group, even though the effects were less pronounced in the HL group. We discuss the implications of these results for our understanding of the reciprocal, dynamic, and multi‐factored nature of parent–child interactions.